Bodies coordinating cooperation and liaison within the framework of official food controls - selected issues - Serlikowska, Agnieszka (Przegląd Prawa Rolnego, 2023)
The aim of the considerations was to define the concept of bodies coordinating cooperation and contacts within the framework of official food controls and to answer the question whether the Polish legislator has satisfied the obligation of appointing them. Analysing the state of affairs in individual EU Member States, the authoress points to the inconsistent approach to the fulfilment of the obligation, which is also present in Polish regulations. She concludes that the Polish legislator has only partially satisfied it, having introduced regulations governing the appointment of co-ordinating bodies only in six of the ten areas identified in the EU regulation. It is therefore necessary to precise relevant provisions in the remaining four areas and to designate an additional body responsible for the controls applicable to animals and goods imported into or exported from the European Union.